Gambaran Perilaku Hidup Bersih dan Sehat pada Rumah Tangga di Kecamatan Solor Barat Kabupaten Flores Timur - Maria Eviliana Gelu Krowin; Marylin Susanti Junias; Indriati A. Tedju Hinga (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Clean behavior on household is an effort to made the family and awaken to each members of family has to volition and ability to PHBS practice,until all members of family could maintain and improve their health, prevent the risk of disease and threat of disease from themselves protectingand play an active role in themovement of  public health. The aim of this research how to knows the description of clean behavior on household at west Solor subdistrict,east Floresregency. The type of this research are used quantitative descriptive. As many as 66 are sampels household used in this research. The data collection techniques used simple random sampling. The data analysis used univariant analyse. The result of this research shows as much 20 (30%) PHBS households. The indicator of PHBS household at west Solor subdistrict,east Flores such as 66 (100%) childbirth assisted by health personels, such as 39 (59%) exclusive breasffeeding, such as 66 (100%) weighing babies and toddlers, such as 62 (93%) used of clean water, such as 62 (93%) wash hands with soap, such as 41 (62%) used healthy latrines, such as 60 (90%) eradicating mosquito larvae, such as 33 (50%) consume the fruits and the vegetables every day, such as  66 (100%) daily physical activity, and the 44 (67%) no smoking in the house. Is the recommended for public health center at Ritaebang to put on community emphasis and gift active attention to carry out PHBS household in every villages in west Solor subdistrict, implementation of socialization especially or counseling about exclusive breasffeeding, used healthy latrines, consume the fruits and the vegetables every day, and do not smoke in the house.